Impact of China’s outward direct investment on economic efficiency - Chan, Sok Gee; Har, Wai Mun; Kanapathy, Kanagi (Asian Development Policy Review, 2023)
This paper examines the impact of China’s Outward Direct Investment (ODI) on the world economy in terms of economic efficiency and aims to provide insight for the host economies in strategizing their investment policies. This study employs Stochastic Frontier Approach (SFA) to estimate the impact of China’s ODI on the world for both developed and developing economies. The research encompassed a total of 156 nations for the period spanning from 2009 to 2017. The findings indicate that there is a 13.3% disparity in efficiency between industrialized and developing countries. The results further reveal that the China’s ODI to developing countries contributes to the reduction of inefficiency in both the Cobb-Douglass and Trans log models. Results for developed countries are mixed, with a significant contribution to inefficiency reduction in the Cobb-Douglass model only. Findings in this paper rebuke the general acceptance that ODI is good in everything for the host countries. Instead, ODI will be more beneficial to the host countries to reduce inefficiency if they are at a lower level of development than the home countries. The findings recommend China’s ODI to developing countries, while developed countries may still reap positive spillovers on efficiency with careful selection of the type of ODI from China to match their national economic development agenda.